ZnO gas sensor for testing vinegar acid concentrations - Al-Hardan .N; Abdullah .M.J; A. Abdul Aziz; Ahmad .H (Universiti Kebangsaan Malaysia, 2011)
A ZnO gas sensor was successfully prepared by RF sputtering. The maximum sensitivity of the sensor for vinegar test application was at 400oC. The ZnO based sensor showed good sensitivity for vinegar test in the concentration range of 4% to 9%. The work reveals the ability of using ZnO gas sensor to determine the acid concentrations of the vinegars for food requirements.